Neuropathological and biochemical investigation of Hereditary Ferritinopathy cases with ferritin light chain mutation: Prominent protein aggregation in the absence of major mitochondrial or oxidative stress. (19th June 2020) - Kurzawa‐Akanbi, M.; Keogh, M.; Tsefou, E.; Ramsay, L.; Johnson, M.; Keers, S.; WSA Ochieng, L.; McNair, A.; Singh, P.; Khan, A.; Pyle, A.; Hudson, G.; et al.
Abstract : Aims: Neuroferritinopathy (NF) or hereditary ferritinopathy (HF) is an autosomal dominant movement disorder due to mutation in the light chain of the iron storage protein ferritin (FTL). HF is the only late‐onset neurodegeneration with brain iron accumulation disorder and study of HF offers a unique opportunity to understand the role of iron in more common neurodegenerative syndromes. Methods: We carried out pathological and biochemical studies of six individuals with the same pathogenic FTL mutation. Results: CNS pathological changes were most prominent in the basal ganglia and cerebellar dentate, echoing the normal pattern of brain iron accumulation. Accumulation of ferritin and iron was conspicuous in cells with a phenotype suggesting oligodendrocytes, with accompanying neuronal pathology and neuronal loss. Neurons still survived, however, despite extensive adjacent glial iron deposition, suggesting neuronal loss is a downstream event. Typical age‐related neurodegenerative pathology was not normally present. Uniquely, the extensive aggregates of ubiquitinated ferritin identified indicate that abnormal FTL can aggregate, reflecting the intrinsic ability of FTL to self‐assemble. Ferritin aggregates were seen in neuronal and glial nuclei showing parallels with Huntington's disease. There was neither evidence of oxidative stress activation nor any significant mitochondrial pathology in the affected basal ganglia. Conclusions: HF shows hallmarks of a protein aggregation disorder, in addition to iron accumulation. Degeneration in HF is not accompanied by age‐related neurodegenerative pathology and the lack of evidence of oxidative stress and mitochondrial damage suggests that these are not key mediators of neurodegeneration in HF, casting light on other neurodegenerative diseases characterized by iron deposition.